RemoteHealthConnect: Innovating patient monitoring with wearable technology and custom visualization - Sasipriya Arun; Edward R. Sykes; Syed Tanbeer (Digital Health)
Objective This paper introduces RemoteHealthConnect , a novel web-based healthcare system designed to enable healthcare professionals to monitor patients remotely with enhanced efficacy. Central to our system is its integration with the Vitaliti™ wearable, equipped with biosensors for real-time vital signs monitoring. RemoteHealthConnect distinguishes itself by offering advanced, custom visualizations for interactive engagement with medical data, facilitating rapid clinical decision-making through intuitive access to vital signs and trends. The primary research question we sought to answer was: ‘Which design of vital sign visualizations is most effective in improving intuitive and rapid understanding for healthcare practitioners?’ Methods An iterative agile/SCRUM methodology was employed in the design and development of RemoteHealthConnect . We describe the architectural design of our web-based application, data visualization techniques, and user interface design. A user interface/user experience (UI/UX) study was conducted to assess the efficacy of our system. Results The usability study revealed the system's capacity to translate complex bedside data into accessible, real-world visualizations, promoting efficient pattern recognition and anomaly detection. This is crucial for enhancing clinician performance, regardless of the patient's location. The paper further details a usability study involving healthcare practitioners to ascertain RemoteHealthConnect's efficacy. The System Usability Scale (SUS) assessment yielded a score of 71.5, indicating high usability. This score is significant, positioning our system above the average usability threshold for healthcare technologies, and suggesting it as a valuable tool for remote patient monitoring. Conclusion Our web-based healthcare system and findings from the usability study contribute to the domains of Mobile Health (mHealth) and e-Health by advancing remote monitoring capabilities and offering a promising avenue for healthcare IT to improve patient care and clinician workflow.